AB0300 Ultrasound evaluation of ankle and foot joints in rheumatoid arthritis. (12th June 2018) - Fellous, S.; Rkain, H.; afilal, S.; Tahiri, L.; Alami, N.; Guieu, R.; yves, J.; Allali, F.; Hajjaj-Hassouni, N.
Abstract : Background: The foot and the forefootin particular are often one of the first areas to be affected by rheumatoid arthritis. The joint destruction develops not only as a result of synovitis but also as a result of specific biomechanical stresses leading to deformity Objectives: Evaluate the prevalence of ultrasound signs of rheumatoid arthritis in the joints of the ankle and foot. Methods: This is a cross-sectional study that included 14 consecutive patients (100% female, mean age 55.3 years) with rheumatoid arthritis (median duration of progression of 13.5 years, mean specialised care of 2.1 years). A grey and Doppler ultrasound study was performed by looking for effusions, synovitis, Doppler activity and bone erosions in the joints of the ankle and foot. Results: 28 feet were studied with an ultrasound evaluation of 308 joints. The prevalence of ultrasound signs of RA are shown in table 1 and 2. Conclusions: This study describes the various ultrasound signs at the joints of the ankle and foot. There is a high prevalence of synovitis in the ankle and hindfoot. Doppler activity has been rarely found. A large-scale study compared with a control group is necessary to better interpret and complete these preliminary results. Disclosure of Interest: None declared